Pengaruh Keteladanan Mohammad Hatta dalam Kebijakan Perumahan Rakyat terhadap Kesejahteraan dari Perspektif Islam - Merisa Ayu Pramesti; Mukhsin Achmad (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores Mohammad Hatta's influence on housing policies in Indonesia, highlighting his integration of Islamic principles into public policy to enhance societal welfare. Hatta viewed housing as a fundamental human right that extends beyond physical needs to encompass spiritual and social dimensions. Grounded in Islamic values such as justice (‘adl), trust (amanah), and solidarity (ta'awun), his policies aimed to ensure equitable access to adequate housing, particularly for low-income communities, while promoting holistic well-being. Hatta’s vision aligned with Islamic teachings that emphasize fairness and state responsibility in fulfilling basic human rights, as reflected in QS. An-Nisa: 58. His ideas inspired initiatives like the Sejuta Rumah (One Million Houses) Program and Tapera (People’s Housing Savings), which address housing disparities and support societal harmony. Additionally, Hatta championed cooperative-based housing development, fostering community participation and mutual assistance, which not only ensured affordable housing but also empowered local economies. By integrating Islamic principles into housing policies, Hatta demonstrated how public policy could balance material, social, and spiritual needs to achieve sustainable societal welfare. His approach offers a valuable framework for future housing programs to promote justice, inclusivity, and collective prosperity.